A study on factors and outcome of unscheduled early revisit to Emergency Department of Hospital USM - Ling, Loi Siew (2018)
Introduction: Unscheduled revisits to the emergency department (ED) may present a considerable additional workload. This study investigated the risk factors contributing to adverse event during unscheduled early revisit to ED Hospital Universiti Sains Malaysia (USM). Methods: A retrospective cohort study was conducted from January 2014 to January 2015 to character the nature of unscheduled early revisits to ED Hospital USM. It included all patients 18 years old and above, revisited ED within 9 days post discharge from ED. Results: Data was collected from 492 case records. The rate of ED unplanned revisits within 9 days of previous ED discharge was 0.66% for the study period. Risk factors for revisit included advance age, pre-existing co-morbids, duration spent during first ED visit and health care system related error. The independent predictors of morbidity were diabetes mellitus (OR, 2.07; 95% CI, 1.08-3.96), respiratory disease (OR, 2.42; 95% CI, 1.18-4.98), gastrointestinal disease (OR, 5.93; 95% CI, 1.29-27.35), nervous system disease (OR, 4.65; 95% CI, 1.27-17.02), duration spent more than 6 hours during first ED visit (OR, 3.05; 95% CI, 1.53-6.07), and medical error leading to admission (OR, 8.85; 95% CI, 4.43-17.67). The overall mortality rate was 0.2% (1/492). Conclusion: ED personnel need to be extra vigilant when managing patients with risk factors particularly the modifiable risk factors to curb ED revisit.